Localization of fluconazole in oral cavity by preferential coating of buccoadhesive tablet for treatment of oral thrush - Pathak, Kamla; Sharma, Vijay; Akhtar, Nida; Rastogi, Pragya (International Journal of Pharmaceutical Investigation)
Background: The present research work was aimed at localization of fluconazole in the oral cavity by preferential coating of buccoadhesive tablet for the treatment of oral thrush. Materials and Methods: In order to achieve the aim, buccoadhesive tablets were optimized using 32 full factorial design to study the influence of varying content of chitosan and carbopol 934P (input variables) on the responses. Results: Perturbation plots revealed high sensitivity of the input variables to ex vivo mucoadhesion force and percent cumulative drug release (CDR) whereas the ex vivo mucoadhesion time was less sensitive to the input variables. Based on the highest desirability factor of 0.693 the formulation F9 was identified as the optimized formulation and was preferentially coated with ethyl cellulose (3% w/v) on one tablet face to get F9C. In reference to F9, F9C showed superior mucoadhesive features (P < 0.05) but the % CDR was comparable (f2 = 50.80). The preferential coating (F9C, Jss = 0.812 μg/cm2/h) limited the permeation of fluconazole across goat buccal mucosa by almost half the value of F9 (Jss = 1.34 μg/cm2/h) that could serve as an advantage in establishing high local concentration of drug in the oral cavity, thereby facilitating faster attainment of minimum inhibitory concentration. Scanning electron microscopy and histological analysis established nonirritant potential. The developed formulation was stable and demonstrated antifungal activity against Candida albicans. Conclusion: Thus it can be concluded that preferentially coated buccoadhesive tablets of fluconazole might be considered as a precise approach to localize the drug delivery in oral cavity.
Keywords: Bioadhesive tablets; coated tablet; fluconazole; optimization; perturbation plots; preferentially localized delivery